Face Perception and Learning in Autism Spectrum Disorders - Webb, Sara Jane (Q J Exp Psychol (Hove), 2016)
Autism Spectrum Disorder (ASD) is characterized by impairment in social communication and restricted and repetitive interests (American Psychiatric Association, 2013). While not included in the diagnostic characterization, aspects of face processing and learning have shown disruptions at all stages of development in ASD, although the exact nature and extent of the impairment varies by age and level of functioning of the ASD sample as well as by task demands. In this review, we examine the nature of face attention, perception, and learning in individuals with ASD focusing on 3 broad age ranges (early development, middle childhood, and adolescence/adulthood). We propose that early delays in basic face processing contribute to the atypical trajectory of social communicative skills in individuals with ASD and contribute to poor social learning throughout development. Face learning is a life-long necessity, as the social world of individual only broadens with age, and thus addressing both the source of the impairment in ASD as well as the trajectory of ability throughout the lifespan, through targeted treatments, may serve to positively impact the lives of individuals who struggle with social understanding and information.